Interfaith encounters in America - McCarthy, Kate, 1962- (New Brunswick, N.J. : Rutgers University Press, 2007)
From its most cosmopolitan urban centers to the rural Midwest, the United States is experiencing a rising tide of religious interest. While terrorist attacks keep Americans fixed on an abhorrent vision of militant Islam, popular films such as The Passion of the Christ and The Da Vinci Code make blockbuster material of the origins of Christianity. Beneath the superficial banter of the media and popular culture, however, are quieter conversations about what it means to be religious in America today. Interfaith Encounters in America takes a compelling look at these seldom acknowledged exchanges.
Introduction -- Theories of religious difference : the "experts" map interfaith relations -- Strange bedfellows : multifaith activism in American politics -- When the other is neighbor : community-based interfaith work -- Intimate others : interfaith families making a space for religious difference -- Meeting the other in cyberspace : interfaith dialogue online -- Conclusion.
Includes bibliographical references (p. 217-225) and index.
Description based on print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: United States -- Religion -- 1960-; Religion; USA; Religion; United States; RELIGION / Comparative Religion; Since 1960; Electronic books